THE USE OF SHARED-READING STRATEGY TO IMPROVE STUDENTS' READING COMPREHENSION - Mudasir, - (2014)
This study aims to investigate how shared reading strategy was implemented in the teaching and learning process and how the students responded to this strategy. It was conducted in a class of seventh grades of a junior high school in Cirebon Regency. The experimental group was treated using shared reading strategy and the control group was not. This study applied a quasi-experiment with survey design. The data were obtained from tests, questionnaires, and interview. The tests were conducted to find out the effects of shared reading strategy on improving students' reading comprehension. It was found that the students in the experimental group were better than those in the control group in improving their reading comprehension. The questionnaires were administered to identify the students' responses towards the implementation of shared reading strategy and showed that almost all of the students were interested, motivated, and becoming more active in the learning process.